Strategies for Coping with Work Stress in Early Adolescent Auditors at Indonesia’s State Financial Audit Office I - Majid, Mochamad Yusril Yusuf; Abdurrohim, Abdurrohim; Zamroni, Zamroni (LifeSciFi, 2026)
Early adulthood, ranging from 19 to 40 years, is a transitional period during which individuals entering the workforce must be mentally and physically prepared for diverse and demanding workloads. Auditors at the Indonesian Audit Board (BPK RI) face substantial occupational stress due to high workloads, organizational pressures, and role demands, which can affect their psychological well-being. This study aimed to identify effective stress-coping strategies employed by early adult auditors to manage work-related stress. A qualitative approach was adopted, utilizing interviews, observations, and document analysis. Data were collected from early adult auditors at BPK RI, supplemented by field observations and analysis of personal and official documents. Findings indicated that stressors originated from both internal and external environments, including workload intensity, role conflicts, and organizational expectations. Despite variations in stressors, all participants applied both problem-focused and emotion-focused coping strategies. These strategies effectively reduced stress and enhanced psychological resilience. The study concludes that implementing appropriate coping mechanisms, supported by organizational attention to employees’ primary needs, can improve auditors’ well-being and sustain performance in high-pressure audit environments.